2022
DOI: 10.57046/weda5828
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial effects of aqueous leaf extracts of Senna alata and Dennettia tripetalla in chloroquine-sensitive Plasmodium berghei berghei (NK65) infected mice

Abstract: The antiplasmodial effects of Senna alata and Dennettia tripetalla on chloroquine-sensitive Plasmodium berghei berghei (NK65) were analysed. P. berghei was obtained from National Institute for Medical Research, Lagos, Nigeria, and maintained in the laboratory by serial passage in mice. Chemosuppressive, prophylactic, and curative procedures were used to evaluate the antiplasmodial potentials of the extracts against established infection. A total of 320 albino mice were used for this study. Twenty-five albino m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The curative result is in line with the research done by Onyegeme-Okerenta et al 13 . The result indicated that there was a significant decrease (p<0.05) in the percentage parastaemia with an increase in dosage concentrations of the extract.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The curative result is in line with the research done by Onyegeme-Okerenta et al 13 . The result indicated that there was a significant decrease (p<0.05) in the percentage parastaemia with an increase in dosage concentrations of the extract.…”
Section: Discussionsupporting
confidence: 90%
“…It was discovered to be cytotoxic against breast cancer cell lines (MCF7) and to have substantial antioxidant and antinociceptive activity, as well as antimalarial, antibacterial, antifungal, anti-inflammatory and diuretic property. It is a precursor of synthetic vitamin E and vitamin K1 [49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…The suppressive test was conducted, and the inception was precisely three (3) hours after the infection of mice for a four-day duration using thirty (30) mice. These tests were performed using the method of Onyegeme-Okerentaa et al [19], with a slight modi cation. Groups 1-3 were the control groups treated with 1 mL of normal saline (the negative control), 25 mg/kg of chloroquine (the positive control), and the uninfected and untreated groups (the normal control), respectively.…”
Section: Evaluation Of Antiplasmodial Activity Of Plant Extractmentioning
confidence: 99%
“…The seed, pulp, and bark of H. umbellata are commonly prepared as an infusion and have been reported to be effective against fever, leprosy, sores, menstrual disturbances, and infertility. Additionally, the seeds of this plant are used in the local management of diabetes mellitus (Olumide et al, 2021) while the unripe fruit is used in the management of malaria (Onyegeme-Okerenta et al, 2023). From the evaluation made by various scientists and researchers, it can be deduced that numerous bioactive concept with known biological usefulness is present in the extracts of H. umbellata and might be responsible for the observed biological and pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%